An electronic documentation system improves the quality of admission notes: a randomized trial. (6th June 2016) - Jamieson, Trevor; Ailon, Jonathan; Chien, Vince; Mourad, Ophyr
Abstract : Objective: There are concerns that structured electronic documentation systems can limit expressivity and encourage long and unreadable notes. We assessed the impact of an electronic clinical documentation system on the quality of admission notes for patients admitted to a general medical unit. Methods: This was a prospective randomized crossover study comparing handwritten paper notes to electronic notes on different patients by the same author, generated using a semistructured electronic admission documentation system over a 2-month period in 2014. The setting was a 4-team, 80-bed general internal medicine clinical teaching unit at a large urban academic hospital. The quality of clinical documentation was assessed using the QNOTE instrument (best possible score = 100), and word counts were assessed for free-text sections of notes. Results: Twenty-one electronic-paper note pairs (42 notes) written by 21 authors were randomly drawn from a pool of 303 eligible notes. Overall note quality was significantly higher in electronic vs paper notes (mean 90 vs 69, P  < .0001). The quality of free-text subsections (History of Present Illness and Impression and Plan) was significantly higher in the electronic vs paper notes (mean 93 vs 78, P  < .0001; and 89 vs 77, P  = .001, respectively). The History of Present Illness subsection was significantly longer in electronic vs paper notes (mean 172.4 vs 92.4 words, P  = .0001). Conclusions: An electronic admission documentation system improved both the quality of free-text content and the overall quality of admission notes. Authors wrote more in the free-text sections of electronic documents as compared to paper versions.